SPECIAL ASPECTS OF DELINEATION OF AUTHORITY BETWEEN FIELD AND/OR DESK TAX AUDIT OR AUDIT OF COMPLETENESS OF THE CALCULATION AND PAYMENT OF TAXES ASSOCIATED WITH TRANSACTIONS BETWEEN RELATED PARTIES - N. Mamikonyan (Вестник университета, 2019)
In the modern context monitoring transfer pricing on the part of state authorities and tax adjustments of controlled transactions between associated and independent parties are vital for the economy and budget of the country. The article is devoted to the correct interpretation of the legislation due to the lack of the appropriate delineation of authority conducting field and/or desk tax audit or audit of completeness of the calculation and payment of taxes associated with transactions between related parties.